THE RESPONSE OF CANDIDA ALBICANS AGAINTS RED FRUCTUS PIPER SP - Ester Rampa (DINAMIS, 2013)
There has been done a research about respons of Candida albicans against red fructus Piper Sp extract by invitro at Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences on September 2012. This study aims to determine the inhibitory effects of red fructus Piper Sp against fungus Candida albicans, as well as the most effective concentration of red fructus Piper Sp that has the highest inhibition against fungus Candida albicans. Population in this research were all kinds of betel, and the samples are red fructus Piper Sp. The method used is a disk diffusion with a concentration of 10%, 5%, 2.5% and Fluconazole control, the parameters measured were the inhibition zone or clear zone. The study design used was a completely randomized design (CRD), When the variance analysis showed Fhit> of F. Tabs with α.05 and α .01, then followed by HSD (Honestly significant difference) test. The results show extracts of red fructus Piper Sp can inhibit the growth of the fungus Candida albicans. The most effective concentration to inhibit the growth of Candida albicans is the concentration of 10% with a 17.42 mm inhibition zone on the Red fructus Piper Sp